HAK KEPEMILIKAN SISA KAIN JAHITAN MENURUT TINJAUAN HUKUM ADAT (URF): STUDI KASUS DI DESA GONDANGLEGI WETAN KECAMATAN GONDANGLEGI KABUPATEN MALANG - roisul adib Idakafakamil; Siti Mutawarridah (Jurnal Penelitian Ilmiah INTAJ, 2023)
Not all tailors return the leftover fabric belonging to the customer and the customer never asks for his leftover fabric. So the main problem of this research is about the custom in Gondanglegi Wetan Village towards excess fabric left over stitches, and about the ownership rights of the stitched fabric according to customary law (‘urf). It is a field research. The sources of data used are primary data which is obtained from interviews and observations of researchers, and secondary data which is obtained from books related to the theme. Based on the data of the research obtained, the researchers concluded that the majority of tailors understood that the leftover fabric belonged to the buyer. However, it has become a habit of the community that the residual fabric from the stitches is not returned and the customer never asks the leftover fabric. Therefore, it is regarded as a customary law (‘urf). The right of ownership of the leftover cloth may be owned by the  tailor, because the customer does not ask for it to be returned, so it  is considered a willingness from the customer